Certified Programs and Proofs First International Conference, CPP 2011, Kenting, Taiwan, December 7-9, 2011. Proceedings - Jouannaud, Jean-Pierre.; Shao, Zhong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the referred proceedings of the First International Conference on Certified Programs and Proofs, CPP 2011, held in Kenting, Taiwan, in December 2011. The 24 revised regular papers presented together with 4 invited talks were carefully reviewed and selected from 49 submissions. They are organized in topical sections on logic and types, certificates, formalization, proof assistants, teaching, programming languages, hardware certification, miscellaneous, and proof perls.
Keywords: Computer science; Software engineering; Logic design; Algebra -- Data processing; Artificial intelligence; Computer Science; Logics and Meanings of Programs; Mathematical Logic and Formal Languages; Programming Languages, Compilers, Interpreters; Symbolic and Algebraic Manipulation; Software Engineering; Artificial Intelligence (incl. Robotics).